High Interval Intensity Training in Patients with Left Atrial Myxoma - Al Mungiza, Berthy; Prabowo, Tertianto; Nazir, Arnengsih (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Myxomas are common benign cardiac tumors that can cause life-threatening events. A case of left atrial myxoma, which induced acute myocardial infarction (AMI) and stroke, is very rare. Patient with concomitant cardiac disease and stroke have lower aerobic capacity than patients with cardiac disease or stroke alone. Here, we report a case presented on 41 years old male patient who diagnosed acute myocardial infarction (AMI) and ischemic stroke (IS) which were induced by left atrial myxoma. He came for phase II cardiac rehabilitation (CR) after underwent surgery with fatigue complaint when he walked more than 500 meters and climbed one floor of stairs. A four weeks comprehensive CR was given to this patient, including a supervised high-intensity interval training (HIIT), thrice a week. This report showed that HIIT can improves functional capacity (FC) and quality of life in patients who suffered left atrial myxoma which induced AMI and IS.